2020
DOI: 10.1039/d0ra00184h
|View full text |Cite|
|
Sign up to set email alerts
|

Study on mechanism of elemene reversing tumor multidrug resistance based on luminescence pharmacokinetics in tumor cells in vitro and in vivo

Abstract: The correlation between efflux functionality of ATP-binding cassette transporters and tumor multidrug resistance reversing via elemene was investigated using bioluminescence imaging (BLI) technology and luciferase reporter gene technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…These two approaches have resulted in luciferin analogues with improved characteristics for in vivo imaging, as discussed below. [15], [16], [18], [19], [20], [21], [24], [28], [29], [30], [31], [32], [33], [34], [35], [36], [ Miller et al developed CycLuc1, in which a pyrrolidine moiety is fused to the benzothiazole moiety of DLH2. The wavelength of CycLuc1 is 599 nm (Km = 0.10 and 1.06 μM in Table 2), which is longer than that of DLH2 due to electron donation from the fused N-hetero ring [75].…”
Section: Luciferin Analogues That Produce Nir Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…These two approaches have resulted in luciferin analogues with improved characteristics for in vivo imaging, as discussed below. [15], [16], [18], [19], [20], [21], [24], [28], [29], [30], [31], [32], [33], [34], [35], [36], [ Miller et al developed CycLuc1, in which a pyrrolidine moiety is fused to the benzothiazole moiety of DLH2. The wavelength of CycLuc1 is 599 nm (Km = 0.10 and 1.06 μM in Table 2), which is longer than that of DLH2 due to electron donation from the fused N-hetero ring [75].…”
Section: Luciferin Analogues That Produce Nir Lightmentioning
confidence: 99%
“…Luciferin–luciferase reactions are also used for in vivo real-time monitoring of gene expression, cell numbers, and other biological events. Specifically, firefly BLI has been utilized for in vivo study in numerous mouse models [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. For instance, it has been used to quantify tumor cells [ 37 ] and monitor gene expression in transgenic mouse models [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent biological research, BLI technology has observed biological events in vivo [2][3][4][5][6][7][8]. For example, in cancer research, BLI has been applied to real-time monitoring of gene expression, cell numbers, and other biological events in transgenic mouse models [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%